Síndrome de Esmeraldite: o profissional médico como paciente e o viés de gênero - Buttarello, Arieli Januzzi (Universidade Federal de São Carlos, 2025)
This work begins with a medical term, "Emeraldite Syndrome," which indicates the difficulty medical professionals have in assuming the role of patient when ill. Through bibliography that touches on the issue posed by the term, it discusses medical professional identity and the gender norms that shape it. The theoretical framework is mainly guided by the concepts of hegemonic masculinity, by sociologist Raewyn Connell, and gender performativity, by philosopher Judith Butler. Data collection was carried out through interviews with male and female physicians in order to understand the meanings given to the condition of being a patient within the medical field and their experiences as patients. The analysis concludes that the crisis faced by medical professionals in the condition of being a patient is permeated by reinforcements and tensions in the gender hierarchy, which shape medical practice, the ways in which male and female physicians give meaning to their own experiences and situations of vulnerability and care.
Emeraldite Syndrome: doctor as patient and the gender bias
Keywords: Síndrome de Esmeraldite; Identidade médica; Relação médico-paciente; Masculinidade hegemônica; Performatividade de gênero; Emeraldite Syndrome; Medical identity; Doctor-patient relationship; Hegemonic masculinity; Gender performativity; CIENCIAS HUMANAS::SOCIOLOGIA; 5. Igualdade de Gênero